Sigma receptor modulators: a patent review. (May 2013) - Collina, Simona; Gaggeri, Raffaella; Marra, Annamaria; Bassi, Andrea; Negrinotti, Sara; Negri, Francesca; Rossi, Daniela
<x xml:space="preserve">Abstract</x> Introduction: Sigma receptors are involved in several central nervous system (CNS) disorders, including mood disorders (depression and anxiety), psychosis, schizophrenia, movement disorders (i.e., Parkinson's disease) and memory deficits (i.e., Alzheimer's disease). Recently, the involvement of sigma receptors in neuropathic pain and cancer has also been observed. Areas covered: This review aims at highlighting the research advancements published in the patent literature between 1986 and 2012, dividing patents according to both their time frame and applicants. The review especially focuses on the development of sigma receptor modulators and their application over the years with respect to CNS diseases, neuropathic pain and neurodegenerative pathologies. The literature was sought through Espacenet, Orbit, ISI Web and PubMed databases. Expert opinion: In recent years, considerable progress in the knowledge of the biology and pharmacology of sigma receptors has encouraged research on the potential benefits of sigma modulators in a wide range of pathologies. So far, only few potent agonists and antagonists of sigma receptors are in clinical trial for acute and chronic neurodegenerative diseases (SA4503 and ANAVEX 2-73) or neuropathic pain (E-52862).